Aberrant elevation of FTO levels promotes liver steatosis by decreasing the m6A methylation and increasing the stability of SREBF1 and ChREBP mRNAs. (10th November 2022) - Tang, Zhili; Sun, Chao; Yan, Ying; Niu, Zhoumin; Li, Yuying; Xu, Xi; Zhang, Jing; Wu, Yuting; Li, Yan; Wang, Li; Hu, Cheng; Li, Zhuoyang; et al.
ABSTRACT: Previous studies have indicated an association of fat mass and obesity-associated (FTO) with nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disease worldwide. This study aimed to decipher the complex role of FTO in hepatic lipid metabolism. We found that a decrease in N 6 -methyladenosine (m 6 A) RNA methylation in the liver of mice fed with a high-fat diet (HFD) was accompanied by an increase in FTO expression. Overexpression of FTO in the liver promoted triglyceride accumulation by upregulating the expression of lipogenic genes. Mechanistical studies revealed that FTO could stabilize the mRNAs of sterol regulatory element binding transcription factor 1 (SREBF1) and carbohydrate responsive element binding protein (ChREBP), two master lipogenic transcription factors, by demethylating m 6 A sites. Knockdown of either SREBF1 or ChREBP attenuated the lipogenic effect of FTO, suggesting that they are bona fide effectors for FTO in regulating lipogenesis. Insulin could stimulate FTO transcription through a mechanism involving the action of intranuclear insulin receptor beta, while knockdown of FTO abrogated the lipogenic effect of insulin. Inhibition of FTO by entacapone decreased the expression of SREBF1, ChREBP, and downstream lipogenic genes, ameliorating liver steatosis in HFD-fed mice. Thus, our study established a critical role of FTO in both the insulin-regulated hepatic lipogenesis and the pathogenesis of NAFLD and provided a potential strategy for treating NAFLD.